Cohomology of $q$-deformed Witt – Virasoro superalgebras of the Hom type - Makhlouf, A.; Saadaoui, N. (Ukrains’kyi Matematychnyi Zhurnal, 2026)
UDC 512.5We study Virasoro-type extensions of the $q$-deformed Witt Hom – Lie superalgebras. Moreover, we provide the cohomology of the $q$-deformed Witt – Virasoro superalgebras of the Hom type.